Exploring the Potential of Anticipated Regret as an Emotional Cue to Improve Bowel Cancer Screening Uptake. (2nd February 2017) - Zajac, Ian T.; Duncan, Amy; Freegard, Suzana; Wilson, Carlene; Flight, Ingrid; Turnbull, Deborah
Abstract : Objective . Bowel cancer is currently the second leading cause of cancer-related death in Australia and screening participation is suboptimal. This study examined the role of emotion in the form of anticipated regret (AR) and its relationship to screening intentions. Methods . N = 173 persons aged 45 to 80 years completed a survey measuring demographic variables, readiness to screen, relative importance of health by comparison to other life priorities, satisfaction with current health, and AR if not participating in future bowel cancer screening. Results . AR was a significant predictor of future screening intentions. Those with higher levels of AR were seven times more likely (OR = 7.18) to intend to screen in the future compared to those with lower AR. This relationship was not compromised when controlling for other variables including gender and satisfaction with one's health. AR levels were significantly lower in people who had been screened previously and in those with full health insurance. Conclusions . These results demonstrate that AR is uniquely related to future bowel cancer screening intentions. Future studies should continue to consider this as a useful target for behavioural interventions and identify new ways of delivering these interventions to improve their reach.